2009
DOI: 10.1007/s12223-009-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of bacteria isolated from crops cultivated in a rotation system and a monoculture against Pythium debaryanum and Fusarium oxysporum

Abstract: The effect of crop rotation and monocropping on the occurrence of bacteria with antagonistic activity toward Pythium debaryanum and Fusarium oxysporum was shown. Arthrobacter spp., fluorescent Pseudomonas spp. and actinomycetes were isolated from winter rape, sugar beet and winter barley rhizosphere and bulk soil from the plots of a long-term crop rotation experiment (18 years). The occurrence of mycoantagonistic isolates and their antibiosis level exhibited specificity for the site, crop and crop rotation. My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Similar effects of plants on the abundance of antagonistic Pseudomonas spp. under monoculture were found by Gorlach-Lira and Stefaniak (2009) . Hence, the abundance of the Pseudomonas populations in soil of R. pseudostellariae were seriously affected by monoculture.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar effects of plants on the abundance of antagonistic Pseudomonas spp. under monoculture were found by Gorlach-Lira and Stefaniak (2009) . Hence, the abundance of the Pseudomonas populations in soil of R. pseudostellariae were seriously affected by monoculture.…”
Section: Discussionmentioning
confidence: 95%
“…Due to an extensive distribution of Pseudomonas species in the environment, several studies reported an abundance of antagonistic Pseudomonas species, which controls specialized pathogens that are responsible for disease suppression in soils ( Gorlach-Lira and Stefaniak, 2009 ; Mendes et al, 2011 ). Our study of Pseudomonas -DGGE revealed that the diversity of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also detected differences between treatments with regard to the abundance of bacteria with antagonistic or plant growth promoting capacities. Among the dominant bacteria, Arthrobacter was identified, which is a mycoantagonistic fungi against P. debaryanum and F. oxysporum [50], as well as Streptomyces, which is widely used due to its nitrogen fixing ability, phosphate and potassium solubilization, phytohormone production, and antifungal activity [51]. These fungi were more abundant in soil after faba bean than after wheat cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Different species of Bacillus represented more than half of the identified Fv antagonistic isolates (Additional file 1 : Table S1), as well as the most prominent bacterial populations in this study. Different species belonging to all other genera that showed fungal inhibition in liquid assay (Additional file 1 : Table S1) including Acinetobacter (Magnin-Robert et al 2007 ), Arthrobacter (Cavaglieri et al 2005a ), Enterobacter (van Dijk and Nelson 1997 ; Gopalakrishnan et al 2011 ), Klebsiella (Lynch 1990 ), Lysinibacillus (Trivedi et al 2011 ), Paenibacillus (Nielsen and Sorensen 1997 ), Pantoea (Babalola 2010 ) and Pseudomonas (Gorlach-Lira and Stefaniak 2009 ) are reported to possess antagonistic traits against diverse pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Different Pseudomonas spp. produce a broad array of lytic enzymes, antibiotics, cyanide, siderophores and antifungal compounds (Nagarajkumar et al 2004 ; Weller et al 2007 ; Gorlach-Lira and Stefaniak 2009 ) which can all inhibit pathogens including Fv .…”
Section: Discussionmentioning
confidence: 99%